Isolation and Characterization of Specific Phages to Prepare a Cocktail Preventing Vibrio sp. Va-F3 Infections in Shrimp (Litopenaeus vannamei) - Chen, Ling; Fan, Jiqiang; Yan, Tingwei; Liu, Quan; Yuan, Shengjian; Zhang, Haoran; Yang, Jinfang; Deng, Deng; Huang, Shuqiang; Ma, Yingfei (Frontiers in Microbiology, 2019)
Vibrio is one of the most detrimental agents of shrimp premature death syndrome. Phage therapy for prevention and treatment of Vibrio infections has attracted increasing attentions due to the emergence of antibiotic-resistant bacterial variants. Here, we describe a workflow of preparing a phage cocktail against Vibrio infections for practical applications. Twenty Vibrio strains were isolated from the gut of diseased shrimp and aquaculture wastewater, and five of them were identified as Vibrio alginolyticus causing shrimp vibriosis. Twenty-two lytic phages were then isolated using the above five pathogens as hosts, and five of them showed broad host ranges and high lytic capability against the Vibrio strains. Whole genomic sequencing and phylogenetic analysis of the five phages indicated that they are novel and belong to the Siphoviridae family. The phage cocktail consisting of these five phages showed higher efficiency in inhibiting the growth of pathogenic V. alginolyticus Va-F3 than any single phage in vitro. We then evaluated the performance of the phage cocktail in protecting shrimp against V. alginolyticus Va-F3 infections in situ. The results showed that shrimp survival rates could reach 91.4% and 91.6% in seven days, for the cocktail-treated and the antibiotic-treated groups, respectively. In contrast, the shrimp survival rate of the group without any treatment was only 20.0%. Overall, this study describes a general workflow of how to prepare a phage cocktail and apply it in controlling bacterial infections in the shrimp aquaculture. Knowledge gained from this study will not only help fight against the shrimp vibriosis in practical, but also facilitate the design of phage cocktails with a satisfying performance in controlling other animal diseases in aquaculture.